SYNTHESIS AND EVALUATION OF DEPRESSANT ADDITIVES BASED ON APIS MELLIFERA CHITOSAN AND ACRYLIC ACID–STYRENE COPOLYMER FOR DIESEL FUEL COLD FLOW IMPROVEMENT (International journal of medical sciences, 2026)
Biodiesel and hydrotreated diesel fuels exhibit poor cold flow properties due to n-paraffin crystallization at low temperatures. In this work, environmentally friendly depressant additives based on chitosan from Apis mellifera exoskeletons and acrylic acid (AA)–styrene (St) copolymers were synthesized and evaluated for improving the cold flow properties of hydrotreated diesel fuel. Chitosan was obtained by alkaline deacetylation of chitin (DD = 85–90%), and AA–St copolymers were prepared by free-radical copolymerization with AIBN as the initiator. The effects of monomer molar ratio, reaction temperature, initiator concentration, reaction time, and solvent polarity on copolymer yield and molecular weight were systematically investigated. FTIR, ¹H NMR, and TGA were used for structural characterization. The copolymerization reactivity ratios, determined by the Mayo–Lewis method, were r₁ = 0.21 ± 0.04 (AA) and r₂ = 0.25 ± 0.05 (St), consistent with the known alternating copolymerization tendency of this system (r₁·r₂ ≈ 0.05). The activation energy ranged from 44 to 56 kJ/mol depending on solvent polarity. Optimal synthesis conditions were identified as: 75°C, AA:St = 50:50, 0.7% AIBN, 3 h in DMF, yielding a copolymer with Mw ≈ 8,700 g/mol. The chitosan–copolymer additive at 0.3 wt% reduced the cloud point by 3–5°C, the pour point by 6–10°C, and the cold filter plugging point by 4–7°C. These results suggest that renewable biopolymer-based depressants can moderately improve diesel cold flow properties, though further optimization of molecular weight and alkyl chain architecture is needed for industrially competitive performance.